Rehabilitation of renders of old buildings in Portugal: survey, supporting methodology proposal and case studies - Carvalho, Carmo Gonçalves de (2016)
The main purpose of the research is to present a proposal for a methodology to support the rehabilitation project of renders of old buildings. To achieve the objective it was considered essential to define the main types of participants and aspects to integrate the proposal. The research methodology consists in an inquiry presented to several professional participants in rehabilitation, a market study of materials and products available in Portugal, the design of a methodology proposal and its application to a case study. The inquiry sample totals 24 answers from the targeted professionals. A sequence of relevant supporting procedures consists in the proposal, which aims to provide a supporting methodology to decide and project in this context and also to be tested with its application to the building. This proposal was applied to an old building with load-bearing stone masonry walls and air-lime based renders. It was concluded that the assessment of the building and external renderings’ condition, its diagnosis and of the supporting walls, the definition of intervention, the specification of materials to be used and performance requirements to comply, and also plans for conservation and periodic maintenance, are crucial. From the inquiry, compatibility between materials and complementary roles and points of view of different types of participants in rehabilitation must be highlighted. A proposal for a methodology to support the project could provide useful guidance particularly for architects and construction engineers, and improve the understanding of direct participants on site, therefore contributing for the correct implementation of the intervention.